International Economics - Robert J. Carbaugh (USA South-Western College Pub, 1998)
INTERNATIONAL ECONOMICS combines a clear and concise treatment of international trade and financial theories with contemporary issues and cases that demonstrate the relevance of theory to real-world economic problems. Carbaugh presents theoretical discussions in both verbal and graphical terms. The text is issue-oriented and can be covered in a one-semester or one-quarter course.
Donated by: Anvar Hodjaev
Keywords: Economics